The relationships between abuse, work social support, value-rich work and intrapersonal coping resources in employed women - Baumann, Chiara (My University, 2016)
The present research aimed to illustrate a link between the two domains of work and abuse. It was an investigation into "the various relationships which exist between spouse abuse and intrapersonal and alternative interpersonal coping resources in employed women.The intrapersonal coping resources identified in past literature and currently examined included self-esteem and level of depression. Alternative interpersonal resources provided by the work sphere were also included for investigation; namely work social support and value-rich work. Amixed quantitative-qual itative research design yielded measures on the five variables of spouse abuse, self-esteem, depression, work social support, and value-rich work; as well as on the two dimensions of physical and non-physical violence, and an additional variable of work support obtained from counselling programmes.The final sample consisted of 106 female employees from a variety of occupational groups. A content analysis of information regarding workplace counselling programmes and its effect on self-esteem and depression generated insignificant results. However, quantitative analyses via Pearson's Product MomentCorrelation Coefficients, one-way ANOVA's and multiple moderated regressions, illustrated very strong support for the remaining hypotheses. This implied that significant relationships did exist between abuse and the coping resources of self-esteem, depression. work support and value-rich work.
A dissertation submitted to the Faculty of Arts, University of the Witwatersrand, Johannesburg, in partial fulfilment for the requirements of the degree of Master of Arts.
Keywords: Abused women -- Psychological aspects.; Wife abuse.; Women -- Employment -- Psychological aspects.; Work -- Psychological aspects.